The Role of Job Rotation in Reducing Counterproductive Work Behaviors: An Exploratory Study of the Opinions of a Sample of Employees in the General Directorate of Tourism in Sulaimania - Khalid Faeq, Dalia (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The aim of the current study is to investigate the impact of job rotation on reducing employee’s Counter Productive Work Behaviors in general directory of tourism in Sulaimania city - Kurdistan region –Iraq. The current study used a quantitative analysis approach in which a questionnaire was adapted from academic sources. The population of the current study consist of the employees work in general directory of tourism in Sulaimania city and the sample size is (161) employees. In order to achieve the objectives of the study and answer the question the researchers adopted a hypothetical construct reflecting the nature of the correlation and influence relationships between the variables of the study, based on a number of hypotheses which were subjected to a series of statistical tests through the (SPSS Vr. 24), and the results revealed that hypotheses are supported as the independent variable ( job rotation) has a strong positive affect on a dependent variable (Counterproductive Work Behaviors). Based on the conclusions, the current study provides number of recommendations such as: Continuous investigation for elements that develop the systems to face the Counterproductive Work Behaviors in the general directory as well as take advantages from other directories in other ministries.